A ciência de dados e o desenvolvimento de negócios na área de exportação - Pescador, Lucas Lima (My University, 2020)
This study exposes the rate of use of Data Science in the development of export business in the area of International Trade. Bibliographic concepts from the exporting sector were explored, as well as research to characterize Data Science, based on scientific articles related to the area. In addition, a search was made for cases of real companies that use technological tools focused on the Data Science area, in order to generate new ones or improve the performance of existing exports within the scope of the international market. The work similarly presents examples of platforms and techniques originated from Data Science and in what ways they have been used as a differentiating factor in international business. The method chosen to instrumentalize the research was the qualitative study of exploratory character, with the application of three individual interviews, two with professionals in the area of international trade, and another with a professional in the area of technology. The interviews were applied upon on a script of ten questions structured based on the stages of an export process, as well as the phases of the data life cycle. While the analysis and discussion of the extracted results made use of a categorization based on these same two themes. Thus, through the interviews, it is possible to understand that the applicability of the data is present in the export processes of the companies, however it is not yet possible to state that the area is already driven by data. [resumo fornecido pelo autor]
Este estudo expõe o grau de uso da Ciência de Dados no desenvolvimento de negócios de exportação dentro da área de Comércio Internacional. Foram explorados conceitos bibliográficos do setor das exportações, além da realização de uma pesquisa de caracterização da Ciência de Dados, a partir de artigos científicos nacionais e internacionais relacionados à área. Em adição realizou-se a busca de casos de empresas reais que utilizam ferramentas tecnológicas voltadas a este campo no intuito de gerar novas ou melhorar o desempenho de exportações já existentes no âmbito do mercado internacional. O trabalho similarmente apresenta exemplos de plataformas e técnicas originadas da Ciência de Dados e de que forma estas estão sendo utilizadas como fator de diferenciação nos negócios internacionais. O método escolhido para instrumentalizar a pesquisa foi o estudo qualitativo de caráter exploratório, com a aplicação de três entrevistas individuais, duas com profissionais da área de Comércio Internacional, e uma outra com um profissional da área de tecnologia. A aplicação das entrevistas se deu em cima de um roteiro de dez perguntas estruturado com base nas etapas de um processo de exportação, bem como nas fases do ciclo de vida dos dados. Já a análise e discussão dos resultados extraídos valeu-se de uma categorização em cima desses mesmos dois temas. Assim por meio das entrevistas é possível compreender que a aplicabilidade dos dados está presente nos processos de exportação das empresas, porém ainda não é possível afirmar que a área já é movida por dados. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Exportação; Negócios